PENGARUH SILENT READING TERHADAP PENINGKATAN KECERDASAN KOGNITIF PESERTA DIDIK - Sufinatin Aisida (AL-AUFA: JURNAL PENDIDIKAN DAN KAJIAN KEISLAMAN, 2020)
Reading habits must become a culture, especially ini educational institutional such as schools, the reading habits has been determined by the goverment in accordance with UU RI Nomor 20 pasal 4 ayat 5 tahun 2003 about the national education system. Many factors affect the level of cognitive intelligence ofÂ  students, one of wich is silent reading. Reading this silent make it easier for students to understand the knowledge they get from books and teacher information, one of the schools that has implemented silent training is YPM Junior High School, this silent reading activity provides a special time for silent reading before starting lessons. As for the objectivites to be achieved in this study are: 1) to find out about silent reading activities at YPM Taman Sidoarjo High School, 2) to find out the level of cognitive intelligence of students in akidah akhlak subjects at SMK YPM 3 Sidoarjo, 3) to find the effect of the implementation of silent reading on the level of cognitive intelligence of students at SMA YPM 3 Sidoarjo. This research is a quantitative. As for the data collection techniques using documentation and questionnaires. Data analysis using teh percentage and correlation of the production moment. The result is 1). Implementation of reading a razor blade in SMK YPM 3 Taman Sidoarjo otherwise good enough, because it is in the range of 56-75% this is based on the percentage results with a value of 71% 2) the level of cognitive intelligence of students at SMA YPM 3 Taman Sidoarjo is in the range of 56-75% this based on the percentage results with a value of 68%. Wich is ontherwise good enough. 3). Silent reading gives 34,3% influence on the level of cognitive intelligence of student in the subject of akidah akhlak, in this case it means that 34.3 % of students area able to think, assess, state, expalain and provide examples of subject matter and 65.7% is influenced by other factors that have not been studied by researchers.